Peran Bank Sampah Dalam Meningkatkan Kualitas Lingkungan Di Kelurahan Padang Jati - Sinaga, Prentina Debora; Okta Velia Triana Hutapea; Putri Ananda Asisti; Annisa Febriana; Hafidza Zia (CV. ITTC INDONESIA, 2025)
The waste management issue in Padang Jati Urban Village remains a serious concern due to the low awareness of residents in sorting and managing household waste. Through the Community Service Program (KKN), students from the University of Bengkulu established a waste bank as a participatory and educational solution to improve environmental quality. This program applied a descriptive qualitative method with a participatory approach, involving socialization, waste sorting training, and operational implementation of the waste bank. The results showed increased public awareness, behavioral changes in waste sorting, and economic benefits through waste-saving systems. Although the program still faces challenges such as limited facilities and varying levels of community understanding, it demonstrates strong potential as a sustainable community-based waste management model that can be replicated in other areas.